Drain the swamp: A theory of anti-elite populism - Gabriele Gratton; Barton E. Lee (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2025)
We study a model of popular demand for anti-elite populist reforms that drain the swamp: replace experienced public servants with novices that will only acquire experience with time. Voters benefit from experienced public servants because they are more effective at delivering public goods and more competent at detecting emergency threats. However, public servants' policy preferences do not always align with those of voters. This tradeoff produces two key forces in our model: public servants' incompetence spurs disagreement between them and voters, and their effectiveness grants them more power to dictate policy. Both of these effects fuel mistrust between voters and public servants, sometimes inducing voters to drain the swamp in cycles of anti-elite populism. We study which factors can sustain a responsive democracy or induce a technocracy. When instead populism arises, we discuss which reforms may reduce the frequency of populist cycles, including recruiting of public servants and isolating them from politics. Our results support the view that a more inclusive and representative bureaucracy protects against anti-elite populism. We provide empirical evidence that lack of trust in public servants is a key force behind support for anti-elite populist parties and argue that our model helps explain the rise of anti-elite populism in large robust democracies.
Keywords: 330